ARAB CAMPAIGNS TO THE MIDDLE OASIS: THE POLITICAL SITUATION IN FERGANA AT THE BEGINNING OF THE 8TH CENTURY - Mahmudov Erkinjon Asqaraliyevich (Scholars Digest Publishing, 2024)
The article analyzes the military campaigns of arab troops to Fergana at the beginning of the 8th century, the political situation between the local rulers of Central Asia in this situation.
Keywords: Fergana, arab Caliphate, arab invasion, coalition, Salih ibn Muslim, Sughd, Nasr ibn Sayyor.